The Adventures of Sinbad - Alligator Books (UK, 2006)
Sinbad thirsts for adventure. He is only truely happy on the high sea even though he always sail into disaster. Wild storm,gigantic whales, an ugly troll, slithering snakes, He faces them all and survives. But is his luck about to run out?...
Keywords: Adventure; Juvenile Fiction; Sinbad